2018
DOI: 10.29101/crcs.v26i80.10516
|View full text |Cite
|
Sign up to set email alerts
|

Orientación vocacional en la infancia y aspiraciones de carrera por género

Abstract: El objetivo del trabajo es identificar las áreas de estudio y los factores que toman en cuenta los infantes al registrar sus aspiraciones de carrera u ocupación. La investigación se fundamenta en las teorías contextuales y evolutivas del ciclo de vida de las personas e integra las profesiones tradicionales por género; además implementa un proyecto de investigación-acción en grupos de nivel primaria de dos escuelas de Tepatitlán, Jalisco (México). Los resultados develan que los campos del saber continúan eligié… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0
22

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 2 publications
0
6
0
22
Order By: Relevance
“…Ashton (2018) suggested that do possible evolutionary pressures between men and women, which would lead to differences in choices. It should be noted that the fields of professional knowledge continue to present traditional gender biases (Macías-González et al, 2019). These same authors highlight the tendency of women to choose careers in health sciences and social sciences.…”
Section: Introductionmentioning
confidence: 95%
“…Ashton (2018) suggested that do possible evolutionary pressures between men and women, which would lead to differences in choices. It should be noted that the fields of professional knowledge continue to present traditional gender biases (Macías-González et al, 2019). These same authors highlight the tendency of women to choose careers in health sciences and social sciences.…”
Section: Introductionmentioning
confidence: 95%
“…Personal preferences and tastes are fundamental in decision making and this choice must be personal, without external influences, such as that of parents. On the other hand, factors such as historical and socioeconomic conditions influence career choices [8]. Young people's career choices are mainly influenced by their perception of competence in the development of specific activities; they value more the activities in which they feel they have a better performance, and which give them greater value.…”
Section: Introductionmentioning
confidence: 99%
“…Young people's career choices are mainly influenced by their perception of competence in the development of specific activities; they value more the activities in which they feel they have a better performance, and which give them greater value. From early childhood, children show professions with which they dream of performing, but when they become adolescents there is a personality identity crisis, so it is necessary to experience different roles and set goals that give meaning to their choices [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…años); 2) Elecciones tentativas (entre 11 y 17 años); 3) Elecciones reales (a partir de los 17 años). Los menores que cursan la etapa de Educación Secundaria Obligatoria y el inicio del Bachillerato y/o Ciclos Formativos quedarían ubicados en el segundo periodo mencionado, caracterizado por las primeras decisiones en torno a su futuro académico, profesional y laboral(Álvarez-Justel, 2017; Duche-Pérez et al 2020) y por la influencia en ellas de impulsos y necesidades(Macías-González et al, 2019).…”
unclassified